2020
DOI: 10.1093/bib/bbaa378
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the natural polyphenol catechin as a multi-targeted agent against SARS-CoV-2 for the plausible therapy of COVID-19: an integrated computational approach

Abstract: The global pandemic crisis, coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has claimed the lives of millions of people across the world. Development and testing of anti-SARS-CoV-2 drugs or vaccines have not turned to be realistic within the timeframe needed to combat this pandemic. Here, we report a comprehensive computational approach to identify the multi-targeted drug molecules against the SARS-CoV-2 proteins, whichare crucially involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 84 publications
(81 reference statements)
1
57
0
Order By: Relevance
“…High frequency of mutation drives viral evolution as well as genome variability and hence enabling viruses to evade the immunity of host and soon develop drug resistance. RNA viruses including SARS-CoV-2 have potential ability to accumulate genomic mutations through an error- prone viral enzyme reverse transcriptase and better adapt inside the host that further creates hurdles in designing antiviral therapeutics against RNA viruses (Mishra et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…High frequency of mutation drives viral evolution as well as genome variability and hence enabling viruses to evade the immunity of host and soon develop drug resistance. RNA viruses including SARS-CoV-2 have potential ability to accumulate genomic mutations through an error- prone viral enzyme reverse transcriptase and better adapt inside the host that further creates hurdles in designing antiviral therapeutics against RNA viruses (Mishra et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The rapidly emerging plethora of computational studies examined SARS-CoV-2-RBD interactions with ACE2 enzyme using the recent crystal structures providing insights into the key determinants of the binding affinity and selectivity. A comprehensive computational approach to identify the multi-targeted drug molecules against the SARS-CoV-2 proteins was recently discussed that synergistically combined MD simulations, free energy landscape analysis and molecular mechanics-Poisson-Boltzmann Surface Area (MM-PBSA) analysis (Mishra et al, 2021). Combined with structural insights this study identified catechin as a novel multi-targeted agent targeting SARS-CoV-2 proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of a drug molecule is largely dependent on molecular interactions at the active site ( Schiebel et al, 2018 ; Mishra et al, 2021 ), and the network of H-bonds plays a crucial role in this interaction. Thus, H-bond interactions between ExoN and drug molecules were calculated ( Chen et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%